Marcus And Burner, Eds., America Firsthand - Schulkin, Carl (Teaching History: A Journal of Methods, 1999)
The fourth edition of America Firsthand delivers exactly what it promises. It "gives voice to ordinary Americans," providing a wide range of eyewitness accounts that permit students to sample "a broad range of human experience." The selections are substantial enough, ranging from six to eight pages each, to allow students "to immerse themselves in each writer's perspective." America Firsthand is intended to help meet "the challenge of connecting traditional chronology with the new materials of social history." Both volumes are organized in accordance with "the traditional markers of United States history" and include accounts of the American Revolution, the Civil War and Reconstruction, the two World Wars, the Great Depression, and the Vietnam War. The editors' introduction to each part announces the theme and briefly explains the relationship of each selection to that theme. The equally concise headnotes preceding each reading are very informative and help contextualize the subject matter for the beginning student.